The DKI Jakarta Provincial Government’s Strategy is Based on Pro-Poor Policies in The KJMU Program - Hardiansyah, Mohammad; Tijan, Tijan (Unnes Political Science Journal, 2023)
The main purpose of establishing a state is to provide welfare for the community. However, this condition is difficult to achieve due to the problem of poverty, not least in DKI Jakarta Province. Responding to this condition, the DKI Jakarta Provincial Government then adopted a policy of fundamental poverty alleviation that tries to affirm the poor through the KJMU program. This study aims to describe the strategy and the factors that can influence the DKI Jakarta Provincial Government’s improving community welfare based on pro-poor policies in the KJMU program. This study uses a qualitative approach with data collection methods such as interviews, observations, and documentation. The analysis of study data is carried out using an interactive data analysis model with stages of data collection, data reduction, data presentation, and conclusion. The results show that the DKI Jakarta Provincial Government carried out a strategic management process with strategy formulation, strategy implementation, and strategy monitoring and evaluation. All these stages are supported by the application of principles of good governance and pro-poor budgeting. However, some factors influence the strategy in the form of the use of DTKS not being maximized; the accuracy of KJMU recipient data; the lack of human resources for program managers; information on the KJMU program that has not been well received by the community; and the discovery of violations of obligations to the KJMU program.